The institutional policy of the University of Amazonia and its impact on the formation of a research professor in social sciences - Queiroz, Luiz Miguel Galvão; Corrêa, Paulo Sérgio de Almeida (Universidade Estadual de Campinas, 2015)
This article aims to analyze the institutional policy at the University of Amazônia - UNAMA and its effects on the formation of a research professor in the area of Social Sciences, by the description of the research activity in the teaching practice in the Course of Social Sciences in that educational institution, represented by the quantitative of scientific production.